FORECASTING PRACTICES IN ACADEMIC IR: METHODOLOGICAL MAINSTREAM AND UNSOLVED PROBLEMS - I. V. Fomin; K. P. Kokarev; B. I. Ananyev; N. Yu. Silaev; A. A. Sushentsov; A. D. Chekov (Vestnik MGIMO-Universiteta)
The article is devoted to the analysis of research tools that are dominant in international relations forecasting. The study is based on quantitative description of 160 prognostic articles from leading journals on international relations for the period from 2006 to 2015. An innovative typology of prognostic studies is proposed and tested. The typology introduces a distinction between «weak prognoses» (probabilistic predictive statements that appear as extrapolations of deductive nomothetical theories) and «strong prognoses» («ideographic» predictions that are formulated as scenarios of possible future developments in specific situations and with specific sets of actors). The study shows that it is the weak prognoses that are the dominant type of forecasts in contemporary international studies. The dominance of the weak approach to forecasting remains total, despite the fact that it is almost two decades ago that its fundamental limitations were demonstrated and a “forward reasoning” approach suggested as an alternative. The methodology of Teaching, Research, and International Policy project was applied for a more detailed epistemological profiling of the field. It showed that academic forecasting in international relations is dominated by quantitative methods and positivist non-paradigmatic approaches. As to the traditional paradigms, it is liberalism that is the most common with Marxism being completely neglected. The described profile of the field follows the trends that are inherent in the discipline of international relations in general. The findings of the study can be interpreted from the perspective of possible tracks for the development of forecasting methods in the Russian school of international relations.